Water quality assessment of Bone River using STORET method - Miftahul Khair Kadim; Nuralim Pasisingi (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
Activities around Bone River, one of the largest rivers in Gorontalo Province, include agriculture, settlement, gold mining, sand excavation, industry, and illegal logging. This research aimed to report the water quality status of Bone River using the STORET method as an index commonly used for measuring pollution levels in a water body, which the Indonesian government regulates, as stated in the Decree of the Minister of Environment, No. 115, 2003. This work involved data from 2021-2023 along the upstream to downstream of the river. There were 12 water quality parameters measured: temperature, TSS, DO, pH, COD, BOD, nitrate, phosphate, ammonia, and the heavy metals (Pb, Cd, and Hg) concentration. This study revealed that parameters met water quality standards for class I and class II: temperature, pH, DO, Pb, and Cd. The index scores ranged from -96 to 0. The upstream area was categorized as good, and the midstream to downstream was recognized as heavily polluted. This pollution level is dominated by organic waste from agricultural and domestic household activities. The concentration value consistently exceeds the quality standard in all data from St 5 to St 12. These two parameters are enough to significantly cause worsening water quality based on the STORET with a total score contribution of -40. BOD and COD parameters contribute the most to the river pollution level.Keywords:Water qualityPollutionSTORETBone River